2016
DOI: 10.1098/rspa.2015.0850
|View full text |Cite
|
Sign up to set email alerts
|

Flow around a rotating, semi-infinite cylinder in an axial stream

Abstract: This paper concerns steady, high-Reynolds-number flow around a semi-infinite, rotating cylinder placed in an axial stream and uses boundary-layer type of equations which apply even when the boundary-layer thickness is comparable to the cylinder radius, as indeed it is at large enough downstream distances. At large rotation rates, it is found that a wall jet appears over a certain range of downstream locations. This jet strengthens with increasing rotation, but first strengthens then weakens as downstream dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Herrada and Pino [17], in their research, presented that non-parallel effects of the base flow have a significant impact on the axisymmetric boundary layer developed on a rotating circular cylinder. Murlidhar et al [18] computed eigenmodes of the axisymmetric boundary layer developed on a rotating circular cylinder at high Reynolds number and found that the increase in the rotation rate increases the wall jet effect. The two dimensional global modes have been computed for the flat-plate boundary layer by numerical solution of two dimensional general eigenvalue problem [10,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Herrada and Pino [17], in their research, presented that non-parallel effects of the base flow have a significant impact on the axisymmetric boundary layer developed on a rotating circular cylinder. Murlidhar et al [18] computed eigenmodes of the axisymmetric boundary layer developed on a rotating circular cylinder at high Reynolds number and found that the increase in the rotation rate increases the wall jet effect. The two dimensional global modes have been computed for the flat-plate boundary layer by numerical solution of two dimensional general eigenvalue problem [10,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Such flows are often due to rotating bodies as, for example, disks [3,4], cones [5,6], or spheres [7]. Here, we consider a semi-infinite cylinder, rotating about its axis and placed in a high-Reynolds-number axial stream, thus inducing a steady, axisymmetric, three-velocity-component boundary layer whose flow field depends on rotation and curvature of the cylinder, as we have already described in an earlier paper [8], henceforth referred to as I. In this paper, we study the stability of this flow for a wide range of parameters, to determine the effects of rotation and curvature.…”
Section: Introductionmentioning
confidence: 99%